Clinical features and prognostic analysis of spontaneous rupture of renal cell carcinoma: a retrospective cohort study - Zhang, Shanhua; Han, Xiaoran; Kong, Shaoqiu; Wang, Jianyu; Wang, Cheng; Wu, Fei; Wu, Haihu; Lyu, Jiaju; Ning, Hao (Frontiers in Oncology, 2025)
BackgroundSpontaneous rupture of renal cell carcinoma (SRRCC) is a rare but critical clinical manifestation characterized by the acute disruption of tumor integrity, leading to extravasation of tumor contents into the perirenal space and associated complications. Understanding its clinical features, risk factors, and prognosis is essential for optimizing diagnosis and treatment.MethodsThis retrospective, single-center study analyzed 37 cases of SRRCC from 165 patients with spontaneous renal tumor rupture treated between April 2014 and June 2024. Clinical, pathological, and laboratory data were collected and analyzed. Kaplan-Meier survival analysis and univariate Cox regression were used to evaluate cancer-specific survival (CSS) and progression-free survival (PFS).ResultsThe median age of SRRCC patients was 49 years (IQR: 38–60), with males accounting for 59.5%. Tumors were predominantly located in the left kidney (70.3%), with clear cell renal cell carcinoma (ccRCC) being the most common histological subtype (56.8%). The median tumor size was 6.5 cm(IQR: 4.1–10.1). The most frequent symptom was flank or abdominal pain (83.8%). Preoperative laboratory tests showed elevated APTT, PT, D-dimer, and fibrinogen levels. Radical nephrectomy was performed in 64.9% of patients, and 48.6% underwent emergency surgery. The median follow-up duration was 60 months (IQR: 27–80). The median cancer-specific survival (CSS) and progression-free survival (PFS) were 60 months (IQR: 27–80) and 49 months (IQR: 19–80), respectively. The 5-year CSS and PFS rates were 80.1% (95% CI: 64.0%–96.2%) and 68.8% (95% CI: 51.4%–86.2%), respectively, as estimated by the Kaplan–Meier method. Prognostic factors significantly associated with CSS and PFS included TNM stage, WHO/ISUP grade, tumor size, perirenal fat invasion, and coagulation abnormalities.ConclusionsSRRCC presents unique diagnostic and therapeutic challenges due to its acute nature and potential for tumor dissemination. Prognosis was associated with tumor characteristics and coagulation markers, while surgical timing and type was not significantly associated with outcomes. Further multicenter studies with larger cohorts are needed to validate these findings and guide clinical management.